GEWE Acceptance, Conjugal Moral Configuration, and the Plurality of Marital Resilience: A Comparative Analysis of Gender Role Ideology in Indonesian Couples - Iwan Zaenul Fuad; Mohammad Fateh; Anindya Aryu Inayati; Abdul Hamid (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study analyzes the influence of gender role ideology on marital stability through two lenses: first, the acceptance of Gender Equality and Women's Empowerment (GEWE); and second, the structure of Conjugal Moral Judgment (CMJ) and Conjugal Moral Resiliency (CMR). The study involved three ideological groups: Egalitarian (N=84), Patriarchal (N=13), and Matriarchal (N=16). In terms of GEWE acceptance, all groups showed generally positive acceptance, with the Egalitarian group having the highest average acceptance, but all groups exhibited uniform rejection toward the Reproductive Health (RH) agenda (M=2.48), indicating a pervasive moral boundary related to the Sanctity foundation. The primary finding is the discovery of a plurality of moral strategies in maintaining marital integrity. Structurally, the Egalitarian group demonstrates a significant Institutional Gap in CMJ, prioritizing individualizing foundations (Care and Fairness) far above binding foundations (Loyalty and Authority). Crucially, this study introduces the concept of CMR and measures it using Standard Deviation (SD) as an indicator of internal moral consensus. The results show that the Patriarchal group employs a Uniform Institutional Strategy with the lowest CMR SD (SD=0.13), signifying the highest moral consensus and predictability. In contrast, the Egalitarian group utilizes a Flexible Individual Strategy with a relatively higher CMR SD (SD=0.16), indicating greater moral negotiation and adaptation. This research contributes substantively by shifting the focus from